Cosmopolitanism in the Middle East as part of global history - Freitag, Ulrike (2010)
Abstract: "This essay combines certain historical insights, stemming from research into the history of Middle Eastern port cities in the 19th and 20th centuries, with some more general concerns regarding international academic cooperation. These are based on my experiences as director of a research center which tries to encourage international cooperation. This paper discusses the issue, firstly, from the point of view of the formulation of research agendas, secondly by having a closer look at the concept and, finally, with regard to certain lessons which impact on any international cooperation." (author's abstract)